Removal of a fractured file beyond the apical foramen using robot-assisted endodontic microsurgery: a clinical report - Mei Fu; Shen Zhao; Xubing Zhou; Benxiang Hou; Chen Zhang (BMC Oral Health)
Abstract Background Endodontic file fractures are common complications of root canal treatment, and requires removal via specialized techniques such as endodontic microsurgery when the file beyond the apical foramen. It is often challenging to precisely and minimally remove a fractured file. Recently the use of dental autonomous robotic system (ATR) has shown promise in precisely and minimally in dental surgery. Therefore, this case details a technique for using the ATR system to precisely and minimally guide the removal of a fractured file beyond the apical foramen. Case presentation A 48-year-old male patient, with no evidence of bone defects, was diagnosed with a file fractured completely beyond the apical foramen during root canal treatment of the right maxillary lateral incisor. Patient information was used to incorporate a digital model into preoperative planning software to develop a surgical strategy. The ATR system employs spatial alignment methods for registration, directing the robotic arm to independently locate the fractured file in accordance with the surgical plan. To maximize minimally invasive surgery, the long fractured file was removed in two stages. After removing the bone and fracture file, the clinician performed suturing under a microscope. No complications were observed during the surgery, and the treatment appeared to be successful based on the 9-month follow-up evaluation. Conclusions The ATR system enables precise localization of the fractured file beyond the apical foramen with intact cortical plates. This technology has the potential to improve positioning accuracy, minimize the need for invasive bone removal, reduce intraoperative time, and facilitate successful endodontic microsurgical procedures.